A rapid passage through a two-active-X-chromosome state accompanies the switch of imprinted X-inactivation patterns in mouse trophoblast stem cells. Issue 1 (December 2015) - Prudhomme, Julie; Dubois, Agnès; Navarro, Pablo; Arnaud, Danielle; Avner, Philip; Morey, Céline
Abstract Background In female mice, while the presence of two-active X-chromosomes characterises pluripotency, it is not tolerated in most other cellular contexts. In particular, in the trophoblastic lineage, impairment of paternal X (XP ) inactivation results in placental defects. Results Here, we show that Trophoblast Stem (TS) cells can undergo a complete reversal of imprinted X-inactivation without detectable change in cell-type identity. This reversal occurs through a reactivation of the XP leading to TS clones showing two active Xs. Intriguingly, within such clones, all the cells rapidly and homogeneously either re-inactivate the XP or inactivate, de novo, the XM . Conclusion This secondary non-random inactivation suggests that the two-active-X states in TS and in pluripotent contexts are epigenetically distinct. These observations also reveal a pronounced plasticity of the TS epigenome allowing TS cells to dramatically and accurately reprogram gene expression profiles. This plasticity may serve as a back-up system when X-linked mono-allelic gene expression is perturbed.